GEOCHRONOLOGICAL BOUNDARIES AND GEODYNAMIC INTERPRETATION OF ALKALINE-MAFIC MAGMATISM IN KUZNETSK ALATAU - Vrublevsky V.V.; Gertner I.F.; Voitenko D.N.; Vladimirov A.G.; Rudnev S.N.; Borisov S.M.; Levchenkov O.A. (My University, 2004)
The available geochronological data indicate three evolutionary stages of alkaline-mafic magmatism in Kuznetsk Alatau (Cambrian-Ordovician, Early-Late Silurian, and Silurian-Devonian boundaries). These data support the observations reported in [14, 15] and assume that Phanerozoic continental growth of the southwestern margin of Siberian continent (in present-day coordinates) occurred in a complex geodynamic setting involving suprasubduction and plume sources.